A review and historical development of analytical techniques to predict aircraft spin and recovery characteristics. Issue 8 (13th July 2020) - Malik, Bilal; Masud, Jehanzeb; Akhtar, Suhail
Abstract : Purpose: This paper aims to present a literature review on analytical research on the prediction of aircraft spin and recovery characteristics, as it progressed from the early years of aviation to current state of the art spin technologies. Design/methodology/approach: Aerodynamic model development approaches that have been generally used in past spin studies are presented. Past contributions in application of these analytical techniques to predict spin and recovery characteristics on various fighters, general aviation and airliners are discussed, thus providing useful reference for researchers embarking aircraft spin research. An overview of the development of spin prevention and spin recovery technologies to mitigate stall/spin susceptibility is presented. Findings: The challenges associated with the presented techniques that prompt possible future research directions are discussed. Originality/value: Despite considerable progress in the recent years, no comprehensive review on the analytical and computational research techniques to predict aircraft post-stall/ spin characteristics has been undertaken in the recent years.